AB0298 LONG-TERM SUPPRESSION OF RAPID RADIOGRAPHIC PROGRESSION AFTER DISCONTINUATION/REDUCTION OF SHORT-TERM BIOLOGIC THERAPY IN PATIENTS WITH EARLY DESTRUCTIVE RHEUMATOID ARTHRITIS ACCOMPANIED WITH EXTENSIVE BONE MARROW EDEMA. (2nd June 2020) - Katayama, K.; Okubo, T.; Sato, T.; Fukai, R.; Yuichi, M.; Yujiro, K.; Ito, H.
Abstract : Background: We reported that short-term (3 or 6 months) treatment with biologics (BIO) group compared with conventional synthetic non-biological disease-modifying anti rheumatic drug (csDMARDs) enhanced group is more effective in the reducing bone marrow edema (BE) and improving structural remission in early destructive RA accompanied with extensive hand BM despite csDMARDs therapy (1). Objectives: Purpose of this extended study is to investigate whether suppression of RRP will maintain after the discontinuation/reduction of short term biological treatment during over 1 year. Clinical registration number; (UMIN-CTR 000013614)(Figure 1 ) Methods: RA disease activity was evaluated by DAS28-ESR after BIO withdrawal/reduction at 12 months. Bone destruction was determined by modified total Sharp scoring (mTSS) using by conventional radiography expressed as yearly progression of mTSS (ΔmTSS/y) at 12 months. Statistical analysis were performed by t-test or Wilcoxon rank sum test using SAS .13.2 software Results: Fourteen out of 23 patients in BIO group achieved improvement of BM (>70% improvement of baseline BE). Three patient continued BIO. Among 11 patient started to discontinuation/reduction of BIO, 7 patients were successful for discontinuation of BIO. Four patients flared (Table 1 ). Mean DAS28-ESR, mean ΔmTSS/y at 0, 12 months after discontinuation in 7 patients were 1.77, 2.02 and -0.66, -0.44, respectively (no significant difference between values in 0 and12 month). In contrast, those in 4 flared patients were 1.91, 4.08 and 0, 1.83, respectively (significant difference). Finally, to resolve baseline prognostic factors for improvement of BE for biological treatment, we compared baseline data between 14 BE improved and 9 BE unimproved RA patients. Low DAS28-ESR at 3 or 6 month (P<0.001) are indicated for significant prognostic factor for improvement of BE, although Low DAS28-ESR at baseline (P=0.07) may associate improvement of BE. Conclusion: Results of this study indicated suppression of RRP will maintain during over 1 year after the discontinuation of short term biological treatment in some patients. We recommend that a short-term treatment with biologics for early RA patients, who are resistant to non-bio DMARDs therapy and at high risk to transit to RRP, will be an effective and economical treatment strategy. References: [1]K. Katayama, T. Okubo, S. Sato et al. Prevention of extensive bone marrow edema and consequent rapid radiographic progression by short term usage of biologics in DMARDs resistant patients with early destructive rheumatoid arthritis. EULAR meeting. FRI 0124(2018). Disclosure of Interests: None declared